PENERAPAN RESTORATIVE JUSTICE TERHADAP TINDAK PIDANA PENCURIAN (STUDI KASUS KEPOLISIAN RESOR PASAMANBARAT) - Hidayat, Roy; Effendi, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Creating a firm, honest and consistent law enforcement attitude towards the will of law and law enforcement for Police investigators is not easy. At least a strong moral commitment is needed, to carry out the task, police investigators are given the authority of a personal nature, as mentioned in Article 7 Paragraph (1) point j and the Police Law Article 16 paragraph (1) point 1 and Article 18, which authorizes "may take other action", with "certain conditions" and it is synonymous with the term police discretion. Like No. LP: 199 / VI / 2016. SPKT.PASBAR. to this writing is First, knowing any theft cases are resolved through restorative justice by Police Pasaman Barat. Second, knowing the process of settlement of criminal theft through restorative justice in Polres West Pasaman. This writing uses the type of legal research method of sociological law research, namely as an effort to see the effect of the validity of positive law on community life, because in this study the author directly mangadakan research on the location or place studied in order to provide a complete and clear picture of the problem studied. While in view of its nature is descriptive, the research that gives a clear and detailed description of the problems studied by the author. From the results of research problems there are two main things that can be concluded. First, the case of theft which was settled through restorative justice by West Pasaman Police in 2016 was the case of theft of palm oil as much as 22 cases, theft of cattle as many as 8 cases and theft of mobile phones as many as 16 cases, with a total of 38 cases. This means that the settlement of a simple criminal offense by promoting restorative justice can be said to be a manifestation of the implementation of progressive law, because basically its main objective is the public interest. In this case, Police investigators West Pasaman Police put the law to be more in accordance with what is wanted by the community, so that the true objective law can be achieved. Second, the process of settling criminal theft through restorative justice in West Pasaman Police is not necessarily applicable to any criminal case, only the criminal act which is light and seen also casuistically, is not feasible, the crime is solved by restorative justice. On the other hand, restorative justice itself is exempted from being applied to cases of criminal offenses that have been perpetrated or perpetrators of perpetrators and have caused unrest for the community at risk of criminal punishment (penal sanctions) as a form of settlement.Keywords: Restorative justice - Discretion - Theft Crime